I am not your negro - Ajgi, Aleksej Gennadievič 1971- (Salzgeber & Co Medien GmbH, 2019)
"Writer James Baldwin tells the story of race in modern America with his unfinished novel, Remember This House." (IMDb)
Bildformat: 16:9
USA/F/B/CH 2016
Keywords: Baldwin, James -- 1924-1987; Dokumentarfilm; Rassismus; Kultur; Schwarze; USA; African Americans / Civil rights / History / 20th century; Civil rights movements / United States / History / 20th century; Racism / United States; Film; DVD-Video